A One‐Step Ionic Liquid Interface‐to‐Bulk Modification for Stable Carbon‐Based CsPbI3 Perovskite Solar Cells with Efficiency Over 15%. Issue 29 (7th September 2022) - Yin, Ran; Wang, Ke‐Xiang; Huo, Xiao‐Nan; Sun, Yan‐Sheng; Sun, Wei‐Wei; Gao, Yu‐Kun; You, Ting‐Ting; Yin, Peng‐Gang
Abstract: Hole transport layer‐free, carbon‐based, all‐inorganic CsPbI3 perovskite solar cells (PSCs) have exhibited great potential in photovoltaic applications owing to their low cost and excellent thermal stability. However, the low power conversion efficiency (PCE) hampers its development, mainly due to the existence of defects inside the CsPbI3 film or at TiO2 electron transport layer/CsPbI3 interface. Herein, these issues were addressed through a facile TiO2 post‐treatment strategy using 1‐butyl‐3‐methylimidazole hexafluorophosphate (BMIMPF6 ) ionic liquid. First, BMIMPF6 can passivate TiO2 /CsPbI3 interface defects by forming strong bond between the electron‐rich N atoms and uncoordinated ions. Second, BMIMPF6 ‐modified TiO2 shows reduced hydrophilicity, inducing decreased heterogeneous nucleation and is favorable for obtaining high‐quality CsPbI3 film. Thirdly, the non‐volatile BMIMPF6 can diffuse to the perovskite film surface during annealing, further passivating defects located at perovskite grain boundaries and surface. Based on this one‐step ionic liquid interface‐to‐bulk modification, the modified device achieves a champion PCE of 15.09%, which is 14% higher than the control device (13.27%). In addition, the modified device also shows enhanced long‐term stability, which remains 96% of initial PCE after 30 days storage in dry air. The work demonstrates the superiority of multifunctional ionic liquid applied to all‐inorganic carbon‐based PSCs, providing a guidance for its commercialization. Abstract : A one‐step interface‐to‐bulk modification with 1‐butyl‐3‐methylimidazole hexafluorophosphate (BMIMPF6 ) is reported for high‐performance and stable carbon‐based CsPbI3 perovskite solar cells (PSCs), which boosts the power conversion efficiency of devices from 13.27% to 15.09%. This work provides a simple and effective way to fabricate carbon‐based CsPbI3 PSCs with high efficiency and stability by one‐step ionic liquid interface‐to‐bulk modification.